The Ponzano-Regge asymptotic of the 6j symbol: an elementary proof - Gurǎu, Rǎzvan (Annales Henri Poincaré, 2008)
In this paper we give a direct proof of the Ponzano-Regge asymptotic formula for the Wigner 6j symbol starting from Racah’s single sum formula. Our method treats halfinteger and integer spins on the same footing. The generalization to Minkowskian tetrahedra is direct. All orders subleading contributions can be computed in this setting. This result should be relevant for the introduction of renormalization scales in spin foam models.
Gesehen am 29.09.2022